KEMAMPUAN PENYELESAIAN MASALAH MATEMATIS SISWA DALAM MATERI FAKTORISASI PERSAMAAN KUADRAT DI SEKOLAH MENENGAH PERTAMA - Saputri, Linda Dwi; Jamiah, Yulis; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the students? mathematical problem solving at Junior High School in academic year 2017/2018. The method used in this research is descriptive method with survey research form. Subjects in this research were students at SMP Negeri 22 Pontianak class VIIID with a number of 29 students. Data collection techniques used were test and interviews. The results of the data analysis showed that students' mathematical problem solving ability were varied, some students were in the high category while the others were in low or medium category. However, generally the students' ability to identifies the elements that were known, asked, and the extent of the required elements were on the medium category (63.45%); to formulate a mathematical problem or to compile a mathematical model were on the low category (48.97%); to apply strategies in solving the problems were on the low category (44,83%); and to explain or interpret the results of problem solving elements on the low category (26.21%).Keywords : Mathematical Problem Solving, Factorization of Quadratic Equations